A 3D cadmium–vanadium bimetallic framework with luminescence properties. (21st June 2017) - Li, Ning; Zhao, Jianguo; Xu, Li; Zhang, Zhong; Hung, Liping; Liu, Yiwei; Lu, Ying; Liu, Shuxia
Abstract : Luminescent properties of a novel cadmium–vanadium bimetallic 3D framework possessing a pillared-layer. Abstract : Herein, a novel cadmium–vanadium bimetallic framework, [(en)Cd2 V2 O7 ] (1 ) (en = ethylenediamine), was hydrothermally synthesized and characterized via IR spectroscopy, elemental analysis, powder X-ray diffraction, thermogravimetric analysis, and X-ray single-crystal diffraction. Compound1 shows an intriguing 3D framework possessing a pillared layer, in which CdO5 N octahedra are corner-shared to generate a 2D layer with 4-membered rings and further extended into a 3D framework. The most fascinating feature of the framework is the connection between layers through double bridges: inorganic V2 O7 dimers and organic en molecules. Note that inorganic and organic double linkers between layers have been first observed in cadmium vanadates. The luminescence properties illustrate an intense, broad emission maximum at λ ≈ 475 nm due to O → V charge transfer in the VO4 units.